Makna dan Fungsi Pembakaran Uang Arwah(金紙) pada Masyarakat Tionghoa Kota Makassar pada Pembelajaran Pengetahuan Lintas Budaya - Ifa Nur Fadillah; Misnawaty Usman; Burhanuddin Burhanuddin (Universitas Negeri Makassar, 2022)
This study is an ethnographic study with a qualitative approach which aims to determine the meaning and function of burning spirit money in the Chinese community of Makassar City in cross-cultural knowledge learning. The informants in this study were three Chinese people in Makassar City who still carry out the tradition of burning spirit money with observation and interview data collection techniques. The results of the interview were written into a transcript which was made into an abstraction. The abstractions that have been made are grouped based on the taxonomy of the research domain, a cultural theme is determined for writing an ethnography. The results of the study concluded that the meaning of burning spirit money was to honor those who had died and that spirit money was used to ransom the King of Hell so that the departed ancestors could be immediately released. Burning spirit money serves so that family members who have died can buy whatever they want in the afterlife. The cultural values contained in the burning of spirit money are religious values and cultural education values. The importance of studying cross-cultural knowledge is to avoid misunderstandings between people with different cultures. Keywords: Spiritual Money, Chinese Society, Cross Culture